Phytochemical Study and Antioxidant Activities of Leaves Extracts from Rhamnus alaternus L. - Boussahel, Soulef; Dahamna, Saliha; Ruberto, Giuseppe; Siracusa, Laura; Harzallah, Daoud (Pharmacognosy Communications)
This study was designed to examine the chemical composition and in vitro antioxidant activities of leaves extracts from Rhamnus alaternus L.; we submitted two extracts (methanolic and aqueous) of different polarity to a deep compositional analysis through the use of an advanced hyphenated technique like LC/Uv-vis-DAD/MS, to our knowledge no metabolic fi ngerprint studies have been done on this species so far. So, we report for the fi st time the complete secondary metabolic fi ngerprint of R. alaternus polar extract, the chromatographic pattern from aqueous extract has several similarities with the methanolic one, two triglycoside fl avonoids were identifi ed in both extracts (kaempferol 3- O -[α-L-rhamnopyranosyl(1→3)- O -α-L-rhamnopyranosyl(1→6)]-β-D-galactopyranoside, rhamnetin 3- O -[α-L-rhamnopyranosyl(1→3)- O -α-L-rhamnopyranosyl(1→6)]-β-D-galactopyranoside), we note the presence of quercetin, kaempferol and rhamnetin derivatives. The samples were also subjected to a screening for their possible antioxidant activities by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and β-carotene-linoleic acid assays, in the first case the IC 50 value was of 0.082 ± 0.0006 mg/ml for the methanolic extract and 0.398 ± 0.007 mg/ml for the aqueous one, in the β-carotene-linoleic acid system, the inhibition values of linoleic acid oxidation were estimated as 89.007 ± 1.914% and 59.639 ± 3.824% for the methanolic and aqueous extract respectively, in both tests the methanolic extract was the most active. On the other hand, total phenolics determination in the test solutions was carried out according to the spectrophotometric Prussian blue assay and the determination of fl avonoids was performed using the method of aluminum trichloride, (AlCl 3 ) all the results indicated that the methanolic extract has higher total phenolics and fl avonoids being of: 33.655 ± 2.503 mg GAE/g for the fi rst method and 61.127 ± 1.217mg EQ/g; 129.681 ± 1.546 mg ER/g, for the second one. According to all these results, we conclude that there is a clear relationship between chemical composition of R. alaternus and its antioxidant activities.
Keywords: β-carotene; Chemical structure; DPPH; Flavonoids